Implementation of the Policy to Accelerate Stunting Reduction in Padang Panjang City - Rahmat Naufaldo; Rahmadani Yusran (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aims to examine the implementation of the stunting reduction acceleration policy in Padang Panjang City. The study is motivated by the continued prevalence of stunting cases, which have significant implications for the quality of human resources. As part of efforts to address this issue, the Indonesian government enacted Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction. This research employed a qualitative approach using a descriptive method. The study was conducted in Padang Panjang City, with the Health Office serving as the primary institution responsible for policy implementation. Research data were collected through interviews with informants selected based on criteria relevant to the objectives of the study. The findings reveal that the implementation of the stunting reduction acceleration policy in Padang Panjang City has not yet been fully effective. Several challenges were identified, including low community participation in stunting prevention programs and inadequate coordination and synergy among relevant stakeholders and government agencies. These challenges have affected the effectiveness of policy implementation in achieving the targeted reduction of stunting rates. Therefore, strengthening community engagement and enhancing cross-sectoral coordination are essential to improve policy implementation and ensure the successful achievement of stunting reduction objectives.